Dental trauma in Turkish children, Istanbul - KARGÜL, BETÜL (BLACKWELL MUNKSGAARD, 2003)
Numerous studies focus on visits to dental clinics for emergent dental problems. Many are all-inclusive, studying traumatic injuries as well as visits for infection and other causes. Epidemiologic studies have focused on the investigation of the prevalence or incidence of dental injury. The patients were evaluated at Pediatric Dentistry, Marmara University Dental School, Istanbul over a 2-year period. For these 300 patients (446 teeth), specific diagnoses were evaluated. Dental injuries that presented most frequently in permanent dentition were crown fractures of enamel only and crown fractures of enamel and dentin. The most frequently presented dental injury in primary dentition were avulsions and crown fractures of enamel. The more frequent treatments for primary teeth were examination only. Bandage restoration, space maintainer were common procedures for permanent teeth.
Keywords: dental trauma; oral epidemiology; tooth injury; INJURIES; MANAGEMENT; TEETH